Pinealectomy abolishes ghrelin staining in the hypothalamus of male rat: An inmumohistochemical study - Kelestimur, Haluk; Canpolat, Sinan; Colakoglu, Neriman; Aydin, Mehmet; Yilmaz, Bayram (Academic Press Inc Elsevier Science, 2006)
[Abstract Not Available]
6th International Congress of Neuroendocrinology -- JUN 19-22, 2006 -- Pittsburgh, PA